Composición florística leñosa y estructural del bosque seco al suroeste de la Provincia de El Oro. - Soto Jaramillo, Eddie Rommel; Quito Pando, Leiner Josue (Machala : Universidad Técnica de Machala, 2024)
The present research aims to analyze the floristic composition, structure and carbon sequestration capacity in three representative sites of dry forests in the southwest of the province of El Oro, Ecuador: The REAr, the Protected Forest of the Arenillas Technical College and a remnant of forest in the Parroquia Palmales. These ecosystems present different degrees of anthropic disturbance, which allows us to evaluate their ecological status. Diversity indices such as the Shannon-Wiener index were used, obtaining values of 2.60 in the REAr, 2.26 in the BPCTA and 1.71 in Palmales. In addition, diameter at breast height (DBH), height (H) and wood density (MD) were measured, parameters that allowed estimating carbon sequestration. The results showed that the BPCTA has the highest biomass and carbon storage capacity (18,436.52 kg of biomass and 9,218.26 kg of carbon), followed by the REAr (9,740.86 kg of biomass and 4,870.43 kg of carbon), while Palmales had the lowest values (5,629.16 kg of biomass and 2,814.58 kg of carbon). The results highlight the importance of conserving dry forests for their biodiversity and their capacity as carbon sinks, contributing to climate change mitigation. They also highlight the need to implement ecological restoration strategies in degraded areas such as the remaining area in Parroquia Palmales.
La presente investigación tiene como objetivo analizar la composición florística, estructura y capacidad de captura de carbono en tres sitios representativos de bosques secos al suroeste de la provincia de El Oro, Ecuador: La REAr, el Bosque Protector del Colegio Técnico Arenillas y un remanente de bosque en la Parrq. Palmales. Estos ecosistemas presentan diferentes grados de perturbación antrópica, lo que permite evaluar su estado ecológico. Se utilizaron índices de diversidad como el de Shannon-Wiener, obteniendo valores de 2,60 en la REAr, 2,26 en el BPCTA y 1,71 en Palmales. Además, se midió el diámetro a la altura del pecho (DAP), la altura (H) y la densidad de madera (DM), parámetros que permitieron estimar la captura de carbono. Los resultados mostraron que el BPCTA tiene la mayor biomasa y capacidad de almacenamiento de carbono 18.436,52 kg de biomasa y 9.218,26 kg de carbono), seguido por la REAr 9.740,86 kg de biomasa y 4.870,43 kg de carbono, mientras que Palmales presentó los valores más bajos 5.629,16 kg de biomasa y 2.814,58 kg de carbono. Los resultados destacan la importancia de conservar los bosques secos por su biodiversidad y su capacidad como sumideros de carbono, contribuyendo a la mitigación del cambio climático. Además, evidencian la necesidad de implementar estrategias de restauración ecológica en áreas degradadas como el remanente en la Parroq. Palmales.
Keywords: BOSQUES SECOS; BIODIVERSIDAD; INDICE DE DIVERSIDAD; CAPTURA DE CARBONO